Field-aligned currents in Saturn's nightside magnetosphere: subcorotation and planetary period oscillation components during northern spring - Bradley,TJ; Cowley,SWH; Provan,G; Hunt,GJ; Bunce,EJ; Wharton,SJ; Alexeev,II; Belenkaya,ES; Kalegaev,VV; Dougherty,MK (Journal of Geophysical Research: Space Physics, 2018)
We newly analyze Cassini magnetic field data from the 2012/2013 Saturn northern spring interval of highly inclined orbits and compare them with similar data from late southern summer in 2008, thus providing unique information on the seasonality of the currents that couple momentum between Saturn's ionosphere and magnetosphere. Inferred meridional ionospheric currents in both cases consist of a steady component related to plasma subcorotation, together with the rotating current systems of the northern and southern planetary period oscillations (PPOs). Subcorotation currents during the two intervals show opposite northsouth polar region asymmetries, with strong equatorward currents flowing in the summer hemispheres but only weak currents flowing to within a few degrees of the openclosed boundary (OCB) in the winter hemispheres, inferred due to weak polar ionospheric conductivities. Currents peak at ~1 MA rad−1 in both hemispheres just equatorward of the openclosed boundary, associated with total downward polar currents ~6 MA, then fall across the narrow auroral upward current region to small values at subauroral latitudes. PPOrelated currents have a similar form in both summer and winter with principal upward and downward fieldaligned currents peaking at ~1.25 MA rad−1 being essentially collocated with the auroral upward current and approximately equal in strength. Though northern and southern PPO currents were approximately equal during both intervals, the currents in both hemispheres were dual modulated by both systems during 2012/2013, with approximately half the main current closing in the opposite ionosphere and half cross field in the magnetosphere, while only the northern hemisphere currents were similarly dual modulated in 2008.